Classification and detection of honey adulteration through corona discharge-induced plasma spectroscopy and electronic plasma nose - Ferrara, Leonardo; Puntoriero, Luis; Boggio, Norberto Gabriel; Vorobioff, Juan; Cáceres, Jorge O.; De Simone, Ricardo; Rinaldi, Carlos Alberto (Research Trends, 2021)
Fil: Ferrara, Leonardo. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina